Bureaucratic Reform in The Area of Legislations: A Study on Halal Product Guarantee Law - Gilang Ramadhan; Amy Yayuk Sri Rahayu (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
Bureaucratic reform in the area of halal product legislation in Indonesia is important because Indonesia's population with a majority of Muslims (87.2%) makes the need for halal products very large. It is necessary to guarantee halal products that enter or circulate in Indonesia. Guarantee of halal products in Indonesia is regulated by the Law No. 33/2014 on Halal Product Guarantee (Halal Product Guarantee Law). The aim of this research is to analyses bureaucratic reform in the area of halal product legislation in Indonesia. By using qualitative methods, the data in this study were obtained by in-depth interviews and literature studies. This research founds that before the Halal Product Guarantee Law was passed, there were many laws and regulations that had long been used to regulate the circulation of halal products. Unfortunately, these regulations are not systemically made, overlapping, partial, and inconsistent. One of the areas of bureaucratic reform in Presidential Regulation 81/2010 on The Grand Design of the 2010-2025 Bureaucratic Reform is a reform of the bureaucracy in the area of legislation. The Halal Product Guarantee Law which was born through bureaucratic reform in the area of legislation is expected to produce regulations that are more orderly, do not overlap and conducive to regulating halal products. Keywords: halal, law, product, reform